Building Energy Renovation and Smart Integration of Renewables in a Social Housing Block Toward Nearly-Zero Energy Status - Yousif, Charles; Gatt, Damien; Caruana, Cedric (Frontiers in Energy Research, 2020)
Like other islands, Malta experiences great challenges to secure its energy supply and independence. Deep renovation of buildings to nearly zero energy and addressing “smart-readiness” are widely believed to contribute to solving such challenges, while meeting the exigencies of the 2018 European Union energy performance of buildings directive (EPBD). Nearly zero energy buildings benchmarks for residential buildings in Malta have been defined using established EPBD cost-optimal methodologies, however these guidelines detailing a one-step and one benchmark definition approach neglects peak loads, building-grid interaction requirements and energy storage. To counteract these inadequacies, this research proposes an innovative multi-criteria approach adapted from ISO 52000-1:2017 standard, which supports the new EPBD requirements for optimizing comfort and addressing energy poverty. This is carried out by first optimizing adaptive comfort in “free-running mode,” before switching to mechanical space heating and cooling. When implementing this approach on a case study of an existing 40-family social housing block undergoing deep renovation, it was found that the discomfort hours have been reduced drastically, while the peak demand for the remaining discomfort hours requiring mechanical heating and cooling has been halved. Despite such positive impact of passive measures, the research has quantitatively demonstrated that given Malta’s temperate climate, such measures have lower impact on the energy rating of the building, when compared to that achieved with active and renewable energy (RE) measures. Thus, the proposed multi-tier benchmarking approach ensures that each energy efficiency measure is appropriately weighted on its own merits, rather than lumping all measures under a single benchmark indicator. With regards to smartness indicators for load matching and grid interaction, a detailed analysis using system advisor model software demonstrated that battery energy storage systems have the capacity to match the RE supply to the demand, although this approach is still far away from being cost-optimal. The research concluded that RE incentives should therefore move away from feed-in tariffs and subsidize direct energy use, storage, and load matching given their high costs. Furthermore, the cost-optimal analysis should also quantify the costs of thermal discomfort, energy poverty and grid mismatch, to ensure a holistic approach to deep renovation of buildings.